2021
DOI: 10.18632/aging.202837
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of long non-coding RNA HOXA11-AS against neuroinflammation in Parkinson's disease model via targeting miR-124-3p mediated FSTL1/NF-κB axis

Abstract: Background: Studies have revealed that lncRNA HOXA11-AS contributes to regulating inflammation, while the role of HOXA11-AS in Parkinson’s disease (PD) remains unclear. Methods: Both in vivo and in vitro PD models were induced. Gain- or loss-assays of HOXA11-AS and miR-124-3p were conducted. The neurological functions, dopaminergic neurons damage, microglia activation of PD mice were measured. Afterwards, the expressions of inflammatory factors were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…HOXA11-AS long non-coding RNA mediated neuronal injury in MPTP cellular model of PD and LPS-induce microglia activation, but miR-124 has opposite effect. HOXA11-AS over-expression increases expression of inflammatory factor and FSTL1, NF-kB and NLRP3 inflammasome while miR-124 is the target of HOXA11-AS and FSTL1 (39). KLF4 and NEAT1 are upregulate in the midbrain of MTPT-HCl mice.…”
Section: Resultsmentioning
confidence: 99%
“…HOXA11-AS long non-coding RNA mediated neuronal injury in MPTP cellular model of PD and LPS-induce microglia activation, but miR-124 has opposite effect. HOXA11-AS over-expression increases expression of inflammatory factor and FSTL1, NF-kB and NLRP3 inflammasome while miR-124 is the target of HOXA11-AS and FSTL1 (39). KLF4 and NEAT1 are upregulate in the midbrain of MTPT-HCl mice.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, the lncRNA/circRNA-miRNA-mRNA regulatory network also exists in microglia and astrocyte mediated neurological diseases, including SCI (Figure 1; Shao et al, 2020; FIGURE 1 | The lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte regulated neurological diseases. Xu S. et al, 2020;Zhao Q. et al, 2020;Cui et al, 2021;Xiang et al, 2021;Chen et al, 2022), TBI (He et al, 2021;Liu N. et al, 2021;Meng et al, 2021), cerebral IRI (Figure 1; Wang et al, 2020c;Yang et al, 2021), stroke (Figure 1; Qi et al, 2017;Han B. et al, 2018;Tian et al, 2021;Zhang M. et al, 2021), epilepsy (Figure 1; Feng et al, 2020;Han C. L. et al, 2020;Wan and Yang, 2020;Xiaoying et al, 2020), neuropathic pain (Figure 1; Chen M. et al, 2020), PD (Figure 1; Cao et al, 2018Cao et al, , 2021, and depression (Figure 1; . We also found that some therapies can impair the ncRNA-glial cell axis and thus inhibit disease development.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA HOXA11-AS is detected to be up-regulated in the substantia nigra area in PD mice. HOXA11-AS over-expression can elevate the levels of inflammatory factors, including, IL-1β, IL-18, IL-6, and TNFα in LPS-mediated BV2 cells (Cao et al, 2021). HOXA11-AS can target miR-124-3p that can target follistatin-like 1 (FSTL1).…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…As long-term hyperglycemia induces inflammatory response, vascular and target organs damage occurs ( Nolan et al, 2011 ), ultimately increasing the incidence of tumors ( Shikata et al, 2013 ; Singh et al, 2021 ), cardiovascular and cerebrovascular diseases ( Kozakova et al, 2019 ; Eckel et al, 2021 ), and other infections ( D'Elia et al, 1991 ; Knapp, 2013 ; Fang et al, 2021 ). NLRP3 inflammasome regulation by lncRNAs is a current research hotspot and has been widely documented in many diseases, such as inflammatory bowel diseases ( Samoilă et al, 2020 ), Parkinson’s disease ( Haque et al, 2020 ; Cao et al, 2021 ), and cancer ( Farooqi et al, 2020 ; Tang et al, 2020 ). Studies indicate that lncRNAs and NLRP3 inflammasome are overexpressed in diabetes complications, implying that lncRNAs could cause inflammatory responses by activating NLRP3 inflammasome ( Hu et al, 2019 ; Farooqi et al, 2020 ; Liu et al, 2020 ).…”
Section: The Mechanism Of Lncrna Involved In Nlrp3 Inflammasome Regulationmentioning
confidence: 99%